Before you knew my name : a novel - Bublitz, Jacqueline (Emily Bestler Books Atria, 2022)
"A psychological suspense novel about two young women who have recently moved to New York City: Alice, who is brutally murdered, and Ruby, who finds Alice and investigates her death"--